Reservoir modeling workflow of central luconia carbonate buildup - Ooi, P.C. (European Association of Geoscientists and Engineers, EAGE, 2016)
The purpose of this research project is to generate a carbonate modeling workflow fully integrating core, modern reef analogues and seismic attributes. Case study is the TX field in Central Luconia. Considering the lack of well log in this field, analogues will be used to spatially distribute the facies. Remote sensing using satellite is applied to study the depo-environment on modern analogues. Conceptual models are first created based on the core (1D) and analogues (2D). Based on the conceptual model, several alternative modeling strategies will be explored to distribute rock types in 3D. To create a meaningful digital model, the algorithms used will be applied by layers/zones following the time where different facies are distributed. Â© 2016 EAGE.